Bio-Based Flexible Solar-Driven Sustainable Generator with Efficient Electricity Generation Enabled by Plant Transpiration System - Kong, Lingli; Lu, Junjie; Luo, Tianwen; Huang, Bai; Fu, Lihua; Lin, Baofeng; Xu, Chuanhui (Nano-Micro Letters, 2026)
The global energy crisis and electricity shortage pose unprecedented challenges. Bio-based solar-driven ionic power generation devices with flexibility, photothermal self-healing and scalability hold great promise for sustainable electricity and alleviating energy crisis. Here, inspired by plant transpiration, a multifunctional bio-based ion conductive elastomer with solar power generation capability was designed by engineered synergy among epoxy natural rubber, cellulose nanofibrils, lithium bis(trifluoromethane) sulfonimide and eumelanin. The film exhibits an outstanding stretchability (1072%) and toughness (22.7 MJ m−3). The favorable synergy of low thermal conductivity, high hygroscopicity and photothermal conversion performance endowed the film with a large thermal gradient under light illumination, driving efficient water transpiration. Furthermore, the excellent interfacial compatibility between eumelanin and matrix facilitates the formation of space charge regions, which further enhances Li+ transport. The film demonstrates excellent evaporation rate (2.83 kg m−2 h−1), output voltage (0.47 V) and conductivity (5.11 × 10–2 S m−1). Notably, the film exhibits remarkable photothermal self-healing performance even in saline environment, achieving 99.6% healing efficiency of output voltage. Therefore, the film demonstrates significant prospects for applications in photo-thermoelectric generation and solar-driven ionic power generation. Highlights: 1 Bio-based solar-driven ionic power generation devices were designed based on the principle of plant transpiration, achieving an evaporation rate of 2.83 kg m⁻2 h⁻1 and an output voltage of 0.47 V. 2 The excellent interfacial compatibility between eumelanin and the matrix facilitates the formation of space charge layer, which significantly enhances Li+ transport. 3 Solar-driven ionic power generation devices possess excellent photothermal self-healing ability (99.6% healing efficiency) and stretchability (1072%) in saline environment.